A Mechano-Activated Cell Reporter System as a Proxy for Flow-Dependent Endothelial Atheroprotection. (September 2018) - Slegtenhorst, Bendix R.; Fajardo Ramirez, Oscar R.; Zhang, Yuzhi; Dhanerawala, Zahra; Tullius, Stefan G.; García-Cardeña, Guillermo
The vascular endothelium plays a critical role in the health and disease of the cardiovascular system. Importantly, biomechanical stimuli generated by blood flow and sensed by the endothelium constitute important local inputs that are translated into transcriptional programs and functional endothelial phenotypes. Pulsatile, laminar flow, characteristic of regions in the vasculature that are resistant to atherosclerosis, evokes an atheroprotective endothelial phenotype. This atheroprotective phenotype is integrated by the transcription factor Kruppel-like factor-2 (KLF2), and therefore the expression of KLF2 can be used as a proxy for endothelial atheroprotection. Here, we report the generation and characterization of a cellular KLF2 reporter system, based on green fluorescence protein (GFP) expression driven by the human KLF2 promoter. This reporter is induced selectively by an atheroprotective shear stress waveform in human endothelial cells, is regulated by endogenous signaling events, and is activated by the pharmacological inducer of KLF2, simvastatin, in a dose-dependent manner. This reporter system can now be used to probe KLF2 signaling and for the discovery of a novel chemical-biological space capable of acting as the "pharmacomimetics of atheroprotective flow" on the vascular endothelium.